Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1095/biolreprod66.6.1743
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Gene and Protein Expression and Its Regulation of Procollagenase and Vascular Endothelial Growth Factor in Human Endometrial Cells1

Abstract: Extensive evidence demonstrates pronounced effects of relaxin on the differentiation of human endometrial cells in vitro. In vivo data in rhesus monkeys suggest a role for relaxin in the development of endometrial vascular architecture. In women, pregnancy can be established and maintained in the absence of circulating relaxin. Thus, local synthesis by the endometrium is necessary if relaxin plays a physiological role in human endometrial function. Although relaxin protein and the prorelaxin C peptide have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
82
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 24 publications
8
82
1
1
Order By: Relevance
“…Other investigators have observed that the effect of relaxin on MMP regulation appears to be cell-type specific. For example, the upregulation, 10,28 downregulation 39,40 and biphasic regulation 27 of MMPs by relaxin have been reported before. In tumor biology, MMPs have been implicated in a variety of processes: a) the degradation of the ECM allowing for cell migration; 41 b) the alteration of the ECM microenvironment resulting in changes of cellular behaviour; 41 and c) the modulation of biologically active molecules by direct cleavage, release from bound stores or modulation of the activity of tissue inhibitors of MMPs (TIMPs).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Other investigators have observed that the effect of relaxin on MMP regulation appears to be cell-type specific. For example, the upregulation, 10,28 downregulation 39,40 and biphasic regulation 27 of MMPs by relaxin have been reported before. In tumor biology, MMPs have been implicated in a variety of processes: a) the degradation of the ECM allowing for cell migration; 41 b) the alteration of the ECM microenvironment resulting in changes of cellular behaviour; 41 and c) the modulation of biologically active molecules by direct cleavage, release from bound stores or modulation of the activity of tissue inhibitors of MMPs (TIMPs).…”
Section: Discussionmentioning
confidence: 70%
“…46,47 The switch towards an angiogenic phenotype facilitates tumor expansion by allowing the tumor to maximize surface area for oxygen transport and nutrient diffusion. 48 Relaxin has been shown to upregulate both transcript and protein of the proangiogenic VEGF 39,49 and NOS species. 50 Therefore, considering that the upregulation of VEGF and NO are implicated in prostate tumor angiogenesis, microcirculation and neovascularization, 7,51 it is possible that relaxin may play an indirect role in this axis during tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Results from various studies provide abundant evidence that relaxin is a potent regulator of the differentiated function of human endometrial cells in vitro (14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Relaxin stimulates the production of prolactin (16,17,19), insulin-like growth factor (18), and insulin-like growth factor binding protein 1 (IGFBP-1) (19), in progestin-primed endometrial stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Relaxin-specific mRNA is detected in human endometrial stromal and glandular epithelial cells, and relaxin protein is secreted into the medium taken from primary cultures of these cell types (14). A role for relaxin in human endometrial function is also supported by findings that relaxin binds specifically and with high affinity to human endometrial cells (15).…”
mentioning
confidence: 94%
See 1 more Smart Citation